Bibliometric analysis using google scholar database: character education research trends in islamic schools - Arsyil Waritsman; Ratna Widianti Utami; Zainul Arief; Baijuri (12 Waiheru, 2025)
This study aims to analyze the trend of character education research in Islamic Schools. The method used is a literature study using bibliometric analysis based on scholarly data. The applications used in the Bibliometric analysis process include Publish or Perish, Mendeley, Microsoft Excel, and VOS Viewer. The results of the Bibliometric analysis found several things, namely (1) research on character education in Islamic Schools does not show a consistent trend from 2018 to 2023; (2) The topic of Islamic Elementary Schools is the most widely carried out topic related to character education research in Islamic Schools; (3) Research topics on character education in Islamic Schools have begun to shift to topics related to thematic learning and (4) Research topics that have the potential for further study related to character education in Islamic Schools are the learning process and policies of the Islamic Schools Headmaster. The results of this Bibliometric analysis contribute to the development of the world of education, especially character education because they contain information on the development of character education in a wide range and contain recommendations for further research that can have an impact on the development of the world of education, especially character education.